Type II photooxidation mechanism of biomolecules using chloro (5,10,15,20-Tetraphenylporphyrinato) indium (III) as a photosensitizer - Silva,André Romero da (2008)
The photooxidation mechanism of bovine serum albumin (BSA), L-tryptophan (Trp) and red blood cells (RBC) by chloro(5,10,15,20-tetraphenylporphyrinato)indium(III) (InTPP) was investigated. The photooxidation rate of Trp, BSA and RBC by InTPP was decreased in the presence of NaN3. The presence of D2O increases the photooxidation rate of Trp and BSA and decreases that of RBC. This decrease is probably related to a reduction of the binding constant between InTPP and RBC in the presence of D2O. No significant change in biomolecule fluorescence or in the percent of hemolysis was observed when radical quenchers (ferricyanide, mannitol and dismutase superoxide) were used. Experiments using electron paramagnetic resonance (EPR) show that only ¹O2 was generated by InTPP. A mechanistic model based on the preferential oxidation of Trp and BSA by singlet oxygen is proposed. The agreement between the experimental data and the kinetic model gives additional support to the predominance of a mechanism via ¹O2 in biomolecule photooxidation by InTPP.